2022
DOI: 10.1186/s12889-022-12634-x
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in sexual and reproductive health services utilization among urban and rural adolescents in southern Ethiopia, 2020: a comparative cross-sectional study

Abstract: Background Although studies on the uptake of Adolescent sexual and reproductive health (ASRH) services in Ethiopia have been conducted they have failed to show the disparity in service uptake among rural and urban settings. Once the extent and determinants of ASRH service uptake in urban and rural contexts are known, it will be crucial to provide evidence-based information and recommendations for potential interventions to reduce the burden of disease and disability among adolescents. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 33 publications
1
20
1
2
Order By: Relevance
“…Being of young age [ 22 , 26 ] and the income status of adolescents' families [ 24 ] were significantly associated with contraceptive utilization. Sociocultural-related factors are the most commonly stated determinants of adolescents' contraceptive uptake and are mentioned in five studies [ 12 , 21 24 ]. Discussion with the family/relatives and parents [ 12 , 21 ], parent disapproval and pressure from partners [ 22 ], and being married or having a partner [ 26 ] were reported as the most important determinants for adolescents' contraceptive uptake.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Being of young age [ 22 , 26 ] and the income status of adolescents' families [ 24 ] were significantly associated with contraceptive utilization. Sociocultural-related factors are the most commonly stated determinants of adolescents' contraceptive uptake and are mentioned in five studies [ 12 , 21 24 ]. Discussion with the family/relatives and parents [ 12 , 21 ], parent disapproval and pressure from partners [ 22 ], and being married or having a partner [ 26 ] were reported as the most important determinants for adolescents' contraceptive uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Healthcare service-related reasons that influence the uptake of contraceptives by adolescents were raised in four studies [ 21 , 22 , 24 , 25 ]. Availability of youth clubs and SRH services [ 21 , 22 ], inconvenient service hours for SRH, and lack of information about FP [ 24 , 25 ] were negatively associated with adolescents' contraceptive utilization. Having knowledge of contraceptive methods [ 23 ] and basic knowledge of SRH [ 21 ] and being informed about contraceptives through media [ 26 ] were knowledge-related determinants of adolescents' contraceptive uptake that were mentioned in three studies and found to be positively associated with adolescents' contraceptive utilization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Por un lado, el personal muestra un alto grado de satisfacción por la articulación con los jóvenes, quienes desde sus propias percepciones y experiencias contribuyeron al desarrollo de propuestas para abarcar la temática y de ese, modo facilitar la comunicación del tema dentro de la comunidad. De igual manera, como lo indica un estudio realizado en la zona rural de Etiopia, el fortalecimiento de sectores -especialmente educación y saludimpulsan esfuerzos para la articulación de la mejora en salud sexual y reproductiva de jóvenes y adolescentes (31).…”
Section: Discussionunclassified